The Influence of Education with Audio-Visual Media on Adolescent Knowledge Level in Kaligentong Village, Gladagsari, Boyolali, Central Java About Preventing of COVID-19 Transmission - Eka Pratiwi; Lusia Murtisiwi (SEKOLAH TINGGI ILMU KESEHATAN NASIONAL, 2021)
In early 2020, the World Health Organization announced Corona Virus Disease-19 (COVID-19) had become a global pandemic. The spread of COVID-19 is very fast and widespread because it is transmitted human to human. Knowledge about preventing the transmission of COVID-19 is very important to reduce the increase in spread of COVID-19, including among adolescents. This study aims to analyse the influence of education with audio-visual media on the level of knowledge of adolescents in Kaligentong Village, Gladagsari, Boyolali regency, Central Java about preventing the transmission of COVID-19. This is a quasi-experimental study with a non-randomized pretest-posttest design with control group. Sampling was done by purposive sampling. The data collection technique was carried out using a questionnaire that was given online using Google form. Respondents in this study were adolescents aged 15-24 years and unmarried, as many as 82 respondents who were divided into two groups, namely the control group and the intervention group. Data were analysed by Wilcoxon, Mann Whitney and intervention effect tests. The results on this study indicate the influence of education through audio-visual media on the level of knowledge of adolescents in Kaligentong Village, Gladagsari, Boyolali about preventing the transmission of COVID-19 with an effect size of 72,3% and shows a significant difference between the experimental group and the control group.Keywords: COVID-19 prevention, adolescents, education, audio-visual media, level of knowledge